Pengaruh Environmental, Social, Governance (ESG) Score Terhadap Financial Performance (Pada Perusahaan yang terdaftar di IDX ESG Leaders Periode 2019-2023) - Wijaya, Erric; Ferli, Ossi; Zahna, Rizka Zahrotul; sitohang, Pebri Monica (Universitas Respati Indonesia, 2025)
The study aims to determine the effect of environmental scores, social scores, and governance scores on financial performance in companies listed on the IDX ESG Leaders. The population in this study were all companies listed on IDX ESG Leaders during 2019-2023. The sample collection technique used was purposive sampling with a total sample of 9 companies. Data was obtained from the official website of each company and the official website of the Indonesia Stock Exchange. Partial test results show that social scores have no effect on financial performance, environmental scores have a significant negative effect and governance scores have a significant positive effect on financial performance. Simultaneous test results show that environmental scores, social scores and governance scores together have a significant positive effect on financial performance